Kazakh traditional types of recreation in terms of cultural study (Journal of Philosophy Culture and Political Science, 2026)
The phenomenon of leisure is an ancient process that belongs to the integral part of human labor culture. However, the scientific study of leisure dates back to the period of development of social sciences. Within the academic community, the notion that "leisure has existed since the advent of machine production" is unanimously accepted. This situation can be explained by the influence of capitalist structures that displaced the medieval way of life and led to the alignment of working hours and leisure time in enterprises, resulting in the emergence of "systematic leisure."Analyzing leisure in medieval Kazakh culture from the perspective of cultural anthropology defines the main objective of this research. The findings of this study may enrich the content of works on Kazakh culture with new ideas, capture the attention of researchers with alternative viewpoints, and potentially contribute to the classification and development of a new model of traditional Kazakh leisure culture.      The novelty of the article's topic lies in the examination of the essence of traditional Kazakh leisure types from the perspective of cultural anthropology. The study employs hermeneutic analysis, historical comparison, and modeling methods. Some of the ancient forms of recreation identified in the article are recommended for use in everyday life.   Key words: work, recreation, children's game, adult game, initiation ceremony